Prevalence and dental effects of infant oral mutilation or Ebiino among 3-5 year-old children from a rural district in Uganda - Norman Musinguzi; Arthur Kemoli; Isaac Okullo (BMC, 2019)
Abstract Background Ebiino, a form of Infant Oral Mutilation (IOM), involves the gauging or enucleation of primary canine tooth buds in infants, and is believed to be a form of remedy to a range of childhood diseases. The effects of this practice have ranged from the child experiencing excessive bleeding, opportunistic infections and even death, besides the potential negative dental effects on primary and the developing permanent dentition of the affected child. The purpose of the study was to establish the occurrence of Ebiino and its dental effects in a rural child-population in Uganda. Methods This study formed part of a larger descriptive cross-sectional study on dental caries and gingivitis, in which 432 children aged 3-5 years old from Nyakagyeme Sub-county, Rukungiri District, Uganda, participated. All the 432 participants (230 males and 202 females, mean age 4.1 SD = 0.8) who had been recruited through stratified random sampling procedure, and whose caregivers had provided a written informed consent, were included in the study. Initially the past dental history of each participant was obtained, and all the children had an oral examination carried out to establish their dental status. Results The data gathered were entered in a computer and analysed using Windows SPSS version 23.0. The results of the analysis showed the prevalence of missing teeth not due to reasons like caries or trauma was 8.1%, with the primary canine being the most commonly missing tooth. These unusual missing teeth were attributed to a traditional practice called Ebiino. Chi-square test showed no statistically significant association of Ebiino with gender and age (p = 0.352 and p = 0.909, respectively). Also found in the study were enamel hypoplasia or damage of some primary canines and/or the primary lateral incisors and first primary molars, as well as displacement of adjacent teeth, a result found to be associated with the practice. Conclusion The practice of Ebiino appears to be endemic within the communities in Rukungiri region in spite of the negative impacts in form of hypoplasia, midline shift, trauma, dental displacement and missing adjacent teeth that it had on the primary dentition of the child.